Isolation of antibiotic producing bacteria from soil and identification by 16S rRNA gene sequencing - Fatima, Sehnin (Brac University, 2020)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2019.